2018
DOI: 10.1007/s13205-018-1276-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage map and QTL identification for adventitious rooting traits in red gum eucalypts

Abstract: The eucalypt species, and, show tolerance to drought and salinity conditions, respectively, and are widely cultivated in arid and semiarid regions of tropical countries. In this study, genetic linkage map was developed for interspecific cross × using pseudo-testcross strategy with simple sequence repeats (SSRs), intersimple sequence repeats (ISSRs), and sequence-related amplified polymorphism (SRAP) markers. The consensus genetic map comprised totally 283 markers with 84 SSRs, 94 ISSRs, and 105 SRAP markers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The second hypothesis was also confirmed; of the 49 microsatellite markers tested in this study that had been developed in E. grandis, E. urophylla, and E. grandis * E. urophylla, 61% were readily transferred to E. pellita, and of these, 17 could be used to construct a linkage map. This met the expectation that eucalypt species have a microsatellite transferability rate of between 40 and 90% [53], and showed that primer pairs developed to date in these other eucalypt species [7,54] have good transferability to E. pellita, despite the apparent lack of synteny between E. pellita and other eucalypt species. A higher transfer rate may have been achieved if PCR conditions had been optimized to avoid non-specific amplification though the testing of a greater number of markers may be a more efficient strategy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The second hypothesis was also confirmed; of the 49 microsatellite markers tested in this study that had been developed in E. grandis, E. urophylla, and E. grandis * E. urophylla, 61% were readily transferred to E. pellita, and of these, 17 could be used to construct a linkage map. This met the expectation that eucalypt species have a microsatellite transferability rate of between 40 and 90% [53], and showed that primer pairs developed to date in these other eucalypt species [7,54] have good transferability to E. pellita, despite the apparent lack of synteny between E. pellita and other eucalypt species. A higher transfer rate may have been achieved if PCR conditions had been optimized to avoid non-specific amplification though the testing of a greater number of markers may be a more efficient strategy.…”
Section: Discussionsupporting
confidence: 56%
“…In the consensus map of E. grandis with an average distance between markers of 8.4 cM, 10 of the 17 markers that contributed to the two linkage maps of E. pellita in this study have also been found in separate linkage groups, in E. grandis [7,11]. Four of the seventeen markers, EMBRA269, 1364, 1811, and 2014, have been used in the construction of a consensus map [11,54,58]. Three, EMBRA351, EMBRA372 and EUCeSSR071, have not previously been incorporated into linkage maps for other eucalypt species.…”
Section: Discussionmentioning
confidence: 68%
“…A subset of 58 primer pairs which were polymorphic in silico in the cross ET86 × EG9 was randomly selected for validating the SSR loci amplification in the 80 full-sib progenies. PCR amplification was performed following the protocol of [29] and the products were separated on 7% polyacrylamide gel electrophoresis. The gel was run at 220 V constant power for 3 h and bands visualised by standard silver staining methods.…”
Section: Genotyping Of a Full-sib Familymentioning
confidence: 99%
“…Previous studies on eucalypt using SSR markers include the development of SSR markers (Grattapaglia et al 2015), genetic diversity (Liu et al 2018b), population structure analyses (Costa et al 2017), genetic linkage map (Sumathi et al 2018), phenotypic and genotypic variation (Padovan et al 2017;Zhou et al 2020), and hybrid purity assessment (Subashini et al 2014). However, in Indonesia, there are limited information and studies on the characterization of eucalypts germplasm based on SSR markers such as the genetic diversity of E. urophylla from 7 islands in eastern Indonesia (Payn et al 2007) and genetic variation of E. deglupta, E. urophylla, and E. pellita from arboretum in Yogyakarta as well as seed garden in South Kalimantan (Nurtjahjaningsih et al 2013).…”
Section: Introductionmentioning
confidence: 99%